The Role of Digital Geography in the Development of Tourism and Tourist Activities - Rubtzov, Vladimir; Zyryanov, Alexander; Firsova, Anastasia; Biktimirov, Niyaz; Marat, Mustafin; Rozhko, Mikhail; Bautista, Hugo (International Journal of Criminology and Sociology, 2022)
Geography and tourism are interconnected and mutually enriching areas. Tourism, as the most susceptible activity to innovations, responds to digital geography by increasing population flows, developing territories, organizing services and leads to an increase in the level of self-organization of activities. Digital technologies are actively penetrating the field of excursions and independent tourism. Mobile audio guides capture the infinite variety of urban space, help young people get involved in the process of developing audio guides, update knowledge of geography, history, culture and form the skill of digital presentation of the knowledge gained. Digital technologies contribute to the intensive development of independent tourism in places inside of the "Infrastructures oecumene ". High rates of inbound tourism are registered in Iceland. Tourism in the form of a family trip by car is largely due to the arrival of digital services for accommodation and meals, car rental. In connection with the development of digital geography in the sphere of tourism, new areas of research are taking shape. The main aim of the study is to investigate the role of digital geography in the development of tourism and tourist activities and attempt to draw some practical and innovative conclusion since the tourism industry has been one of the most lucrative industries over the last decades. In this study, methods of analysis and synthesis of scientific literature, data from a review of audio tours of Perm on the izi.TRAVEL platform, and official tourism statistics from Iceland were utilized to fulfil the aim of the study.